2021
DOI: 10.1038/s41598-021-81690-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric ultrasound findings in acute kidney failure due to rare renal cortical necrosis

Abstract: Renal cortical necrosis (RCN) is a rare cause of acute kidney failure and is usually diagnosed on the basis of characteristic enhancement patterns on cross-sectional imaging. Contrast-enhanced ultrasound (CEUS) offers benefits in patients with kidney failure in the clinical setting including the use of a nonnephrotoxic intravascular contrast agent and the fact that it can be performed at the bedside in critical cases. Therefore, the aim of this study is to investigate whether CEUS can reliably identify typical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
0
9
0
4
Order By: Relevance
“…In the differential diagnosis between renal cortical necrosis (RCN) and renal vein thrombosis (RVT), the Doppler US plays an important role. Spiesecke P. et al [40] have…”
Section: Renal Vein Thrombosismentioning
confidence: 96%
See 1 more Smart Citation
“…In the differential diagnosis between renal cortical necrosis (RCN) and renal vein thrombosis (RVT), the Doppler US plays an important role. Spiesecke P. et al [40] have…”
Section: Renal Vein Thrombosismentioning
confidence: 96%
“…In the differential diagnosis between renal cortical necrosis (RCN) and renal vein thrombosis (RVT), the Doppler US plays an important role. Spiesecke P. et al [40] have shown that the resistive index (RI) is a very important distinguishing feature to separate RCN (RI not measurable due to hypoperfusion) and RVT (RI > 1). However, in unclear cases, the use of a contrast agent, which will demonstrate renal medulla enhancement only in patients with NCR and the absence of enhancement in patients with RVT, may be useful.…”
Section: Renal Vein Thrombosismentioning
confidence: 99%
“…In addition to its good safety profile and simplicity, CEUS is also patient-friendly, has no ionizing radiation, and can enable multiplanar imaging in real time ( 15 , 16 ). Particularly, in patients with acute kidney disease, CEUS is a suitable imaging method since, unlike contrast-enhanced computed tomography (CE-CT) contrast agents containing iodine, ultrasound contrast agents do not cause nephrotoxicity ( 17 ). Scholars are currently using CEUS to diagnose IVL, obtaining more information than conventional ultrasound, particularly the tiny blood inside the lesion, which is critical for IVL differential diagnosis ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly applied method for renal imaging is ultrasonography. It is also a non-invasive, non-ionizing technique, which provides the ability to dynamically image morphological abnormalities with high resolution, to measure blood flow with the Doppler method, and to apply a safe contrast agent to visualize perfusion without harming the kidney [86][87][88][89]. In contrast to MRI, it is widely available and cost-efficient [90].…”
Section: Discussionmentioning
confidence: 99%